Effectiveness of Home Tutoring in Mathematics 6 Under Modular Distance Learning in a Public Elementary School in the Philippines - Galay Jr., Feliciano C. (Future Science / FSH-PH Publications, 2023)
Various issues and concerns raised by parents, students, and teachers about the implementation of Modular Distance Learning were addressed during the Online Kamustahan at a public elementary school where the study was conducted. Parents were particularly concerned about how their children would learn the skills required in their subjects without proper instruction from teachers. The development and implementation of an intervention is one method for addressing students' learning gaps and overcoming learning barriers. This study evaluated the effectiveness of home tutoring as an intervention in teaching Mathematics 6 to modular students in a public elementary school in the Philippines. Experimental research design was used in this study. A set of teacher-made tests were given to fifteen (15) Grade 6 modular students enrolled for the Academic Year 2020-2021. The pre-test and post-test scores were interpreted using mean, mean percent score, summation of x, summation of square x, absolute range, standard deviation, and coefficient of relative variation. Results showed that home tutoring focusing on the students' least mastered skills is an effective intervention in teaching Mathematics 6, with a mastery increase of +44.67%. It is recommended that the school allocate funds for promotional materials, marketing expenses, signage, and incentives for program implementation. and that the school will develop another intervention program to address the students' deficiencies, with a committee in charge of developing, implementing, and evaluating the program.